The Effect of Culture on Perspective Taking - Wu, Shali; Keysar, Boaz (Psychological Science, 2007)
People consider the mental states of other people to understand their actions. We evaluated whether such perspective taking is culture dependent. People in collectivistic cultures (e.g., China) are said to have interdependent selves, whereas people in individualistic cultures (e.g., the United States) are said to have independent selves. To evaluate the effect of culture, we asked Chinese and American pairs to play a communication game that required perspective taking. Eye-gaze measures demonstrated that the Chinese participants were more tuned into their partner's perspective than were the American participants. Moreover, Americans often completely failed to take the perspective of their partner, whereas Chinese almost never did. We conclude that cultural patterns of interdependence focus attention on the other, causing Chinese to be better perspective takers than Americans. Although members of both cultures are able to distinguish between their perspective and another person's perspective, cultural patterns afford Chinese the effective use of this ability to interpret other people's actions.